2001
DOI: 10.1097/00000542-200111000-00007
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Quality of Clinical Trials in Anesthesia

Abstract: Although the quality of clinical trials in four major anesthesia journals has increased steadily during the past two decades, specific areas of trial methodology require further attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…These results are consistent with other areas of health care, including psychiatry [21], palliative care [22], nursing [23], assisted reproduction [24], oncology [25], anesthesiology [26], ophthalmology [27], and drugs and surgery [17].…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with other areas of health care, including psychiatry [21], palliative care [22], nursing [23], assisted reproduction [24], oncology [25], anesthesiology [26], ophthalmology [27], and drugs and surgery [17].…”
Section: Discussionsupporting
confidence: 82%
“…In Table 1 we present the available data from the studies that compared the methodological quality of RCTs in various research fields [3e37; Table is available on the journal's website at www.jclinepi.com]. The included studies reported on the methodological changes that were performed during the years in the RCTs of various biomedical fields, including rheumatology [10, 14,15,33,36], gastroenterologyehepatology [12, 23,24], orthopedics [6,9,17], anesthesiology [19,20,27], surgery [13,32], public health/ health services [29,30], intensive care [16,18] [26], psychiatry [25], radiology [35], complementary medicine [22], and general practice [31]. One study [34] examined meta-analyses conducted on the fields of gastroenterology, cardiology, obstetrics, and smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Further, there has been a tendency to believe the results of small perioperative clinical studies, especially when they demonstrate statistically significant results. This position is supported by the fact that perioperative guideline committees recommended ␤-blockers to patients undergoing noncardiac surgery for a decade based upon the results of small trials demonstrating implausibly large treatment effects.…”
Section: Perioperative Researchmentioning
confidence: 99%